VARIABLE ACTIVE SITE LOOP CONFORMATIONS ACCOMMODATE THE BINDING OF MACROCYCLIC LARGAZOLE ANALOGUES TO HDAC8 - Decroos, Christophe (Biochemistry, 2015)
The macrocyclic depsipeptide Largazole is a potent inhibitor of metal-dependent histone deacetylases (HDACs), some of which are drug targets for cancer chemotherapy. Indeed, Largazole partially resembles Romidepsin (FK228), a macrocyclic depsipeptide already approved for clinical use. Each inhibitor contains a pendant side chain thiol that coordinates to the active site Zn(2+) ion, as observed in the X-ray crystal structure of the HDAC8–Largazole complex [Cole, K. E.; Dowling, D. P.; Boone, M. A.; Phillips, A. J.; Christianson, D. W. J. Am. Chem. Soc. 2011, 133, 12474]. Here, we report the X-ray crystal structures of HDAC8 complexed with three synthetic analogues of Largazole in which the depsipeptide ester is replaced with a rigid amide linkage. In two of these analogues, a 6-membered pyridine ring is also substituted (with two different orientations) for the 5-membered thiazole ring in the macrocycle skeleton. The side chain thiol group of each analogue coordinates to the active site Zn(2+) ion with nearly ideal geometry, thereby preserving the hallmark structural feature of inhibition by Largazole. Surprisingly, in comparison with the binding of Largazole, these analogues trigger alternative conformational changes in the L1 and L2 loops flanking the active site. However, despite these structural differences, inhibitory potency is generally comparable to, or just moderately less than, the inhibitory potency of Largazole. Thus, this study reveals important new structure-affinity relationships for the binding of macrocyclic inhibitors to HDAC8.